The Effect of Green Tea (Camellia sinensis) on Reducing Cholesterol Levels in Hypercholesterolemic Patients at the Working Area of Pangkajene Sidrap South Sulawesi Community Health Centre - Hasliani, Hasliani (Journal of World Future Medicine, Health and Nursing, 2024)
Cholesterol is a component of fatty acids found in the blood. This substance is needed by the body for certain processes for survival. Among other things to form hormones, cells and maintain nerve cells. The purpose of this study was to determine the effect of giving green tea on reducing cholesterol levels in hypercholesterolemia patients in the Pangkajene Health Center work area. The design of this study was a pre-experiment pretest-posttest one group design. The population in this study were all hypercholesterolemia patients in the Pangkajene Health Center work area with sampling techniques using purposive sampling techniques totaling 15 respondents. This research was conducted on April 15-30, 2023. The results showed that before being given the intervention of giving green tea, most of the respondents’ cholesterol levels were in the high category as many as 9 respondents (60%), and the normal category was 7 respondents (46.6%), the conclusion of the study was that there was an effect of giving green tea on reducing cholesterol levels in hypercholesterolemia patients with a p-value = 0.000. Suggestions are expected for people who experience hypercholesterolemia to use green tea as an alternative treatment to lower cholesterol levels.